Dietary astaxanthin for growth and health enhancement of Asian seabass, Lates calcarifer (Bloch, 1790) - Lim, Keng Chin (2020)
Astaxanthin is renowned for its commercial application in numerous industries comprising cosmetic, food, aquaculture, nutraceutical, and pharmaceutical. The freshwater green microalga Haematococcus pluvialis is the richest bio-resource of natural astaxanthin. The supreme antioxidant property of astaxanthin reveals its tremendous potential to offer manifold health benefits amongst aquatic animals. Like many cultured fish species, the intensive farming of Asian seabass Lates calcarifer under stressful circumstances has posed several major problems, including sluggish growth, poor survival, and susceptibility to pathogenic diseases. This study investigated the effects of supplementation with astaxanthin (dose-response manner) on growth performance, survival, hemato-biochemical indices, innate immunity, histopathological responses, and disease resistance of the Asian seabass. A two-stage process was employed for the astaxanthin-rich biomass production of H. pluvialis in the airlift annular photobioreactor. Astaxanthin content was quantitatively determined via the high-performance liquid chromatography (HPLC) analytical method. Four experimental diets, including a control diet (CD), and diets containing various dietary levels of astaxanthin (AX50, 50 mg kg-1 diet; AX100, 100 mg kg-1 diet; and AX150, 150 mg kg-1 diet) supplemented with astaxanthin-containing lyophilized H. pluvialis biomass (~37.94 ± 0.41 mg astaxanthin g-1 dry weight) were produced for different feeding trials. Findings from the first trial revealed that fish exhibited significant linear increments (P < 0.05) in specific growth rate, weight gain, feed utilization efficiency, survival, and serum growth hormone (GH) availability when fed diets with escalating levels of astaxanthin during distinct feeding phases (short-term, medium-term and long-term). Significant positive correlations (P < 0.05) were noted between serum GH level and SGR of fish from all groups following three consecutive feeding phases, denoting a robust cause-and-effect relationship. Circulating serum GH concentration was recognized as a sensitive biomarker of growth performance in the Asian seabass. Moreover, in the second trial, fish displayed profound enhancements (P < 0.05) in hematological indices (white blood cell (WBC) count, red blood cell (RBC) count, hemoglobin, and hematocrit) when fed diets with elevated doses of astaxanthin over different phases of feeding (short-term, medium-term and long-term). Serum concentrations of alanine aminotransferase (ALT), aspartate aminotransferase (AST), glucose, cholesterol, triglyceride, and cortisol in the treated fish reduced significantly (P < 0.05) with increasing dietary inclusion levels throughout the specified feeding phases. Correspondingly, the supplemented fish registered remarkably higher (P < 0.05) serum total protein content. Immunological parameters (lysozyme activity, phagocytic activity, respiratory burst activity, and total serum immunoglobulin) of fish were significantly stimulated (P < 0.05) in response to dietary intervention with astaxanthin. Experimental infection with Vibrio alginolyticus unveiled that supplemented fish demonstrated significant improvements (P < 0.05) of hematological parameters (WBC and RBC counts, and hemoglobin and hematocrit levels) when fed diets with elevating supplemental doses of astaxanthin through distinct post-infection periods (0-, 7-, and 14-day). Furthermore, the administration of dietary astaxanthin at escalating levels markedly enhanced (P < 0.05) the serum biochemical profile (AST, ALT, glucose, cortisol, cholesterol, and triglyceride contents) of challenged fish, resulting in better welfare. Significantly higher (P < 0.05) contents of serum total protein were discernible in supplemented fish, as opposed to the control. Additionally, non-specific defense mechanisms (lysozyme activity, phagocytic activity, respiratory burst activity, and total serum immunoglobulin) of challenged fish were pronouncedly elicited (P < 0.05) following the ingestion of astaxanthin. Histopathological alterations in target organs (liver, kidney, and spleen) of challenged fish were observed to be significantly reduced progressively (P < 0.05) with increasing dietary intake of astaxanthin. Besides, supplementation with dietary astaxanthin significantly augmented (P < 0.05) the post-challenge survival rate of fish.